Contributions of Repetitive Movements to Tennis Elbow Risk in Badminton Players - Lisa Grafita; Farid Rahman (Universitas Pendidikan Indonesia, 2023)
Regular practice of badminton players will lead to the formation of repetitive movement patterns as a significant factor causing outer elbow pain, commonly referred as tennis elbow. This study was aimed to identify the contribution of repetitive movements to tennis elbow risks in badminton players, to examine the relationship between repetitive movements and tennis elbow risks, and to investigate the differences of tennis elbow risk based on the repetitive movement status and the player status. The method used was the observational study with a correlational approach involving 122 players of student badminton organization, known as UKM, from four universities selected using the purposive and cluster sampling methods. The dependent variable of this study was the tennis elbow risk, while the independent variables were repetitive movements and the player status. The ordinal linear regression statistical test results obtained a p-value estimated parameter of p = 0.418 and a pseudo R-Square value of 11.4%. Spearman statistical test was obtained (p=0.020) with a value of r = -0.210. The Kruskal-Wallis H statistical test was obtained (p=0.040). The Mann-Whitney statistical test was also obtained (p=0.005). Repetitive movements contribute to the risk of tennis elbow in badminton players and affect the condition. In addition, there is a weak relationship between repetitive movements and tennis elbow. Repetitive movement status and player status affect the risk of tennis elbow in badminton players.